2019
DOI: 10.1002/ijc.32607
|View full text |Cite
|
Sign up to set email alerts
|

The functional interlink between AR and MMP9/VEGF signaling axis is mediated through PIP5K1α/pAKT in prostate cancer

Abstract: Currently, no effective targeted therapeutics exists for treatment of metastatic prostate cancer (PCa). Given that matrix metalloproteinases 9 (MMP9) and its associated vascular endothelial growth factor (VEGF) are critical for tumor vascularization and invasion under castration‐resistant condition, it is therefore of great importance to define the functional association and interplay between androgen receptor (AR) and MMP9 and their associated key survival and invasion pathways in PCa cells. Here, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 28 publications
4
36
0
Order By: Relevance
“…By contrast, ISA-2011B exhibited a significant inhibitory effect on the proliferation of PC-3 cells that had a high level of PIP5K1α ( Figure 6 f). These results are consistent with our recent reported studies showing that ISA-2011B treatment resulted in the reduced proliferation and invasiveness of PCa cells [ 25 ].…”
Section: Resultssupporting
confidence: 94%
“…By contrast, ISA-2011B exhibited a significant inhibitory effect on the proliferation of PC-3 cells that had a high level of PIP5K1α ( Figure 6 f). These results are consistent with our recent reported studies showing that ISA-2011B treatment resulted in the reduced proliferation and invasiveness of PCa cells [ 25 ].…”
Section: Resultssupporting
confidence: 94%
“…MMPs have been shown to be important targets for treating metastatic prostate cancer. For example, Larsson et al found that MMP9 can increase the aggressiveness of metastatic cancer and promote the growth of metastatic tumors by interacting with other factors [15]. Li et al found that reducing the expression of MMP-9 in prostate cancer cells was accompanied by a decrease in cell invasion and migration [16].…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, MMP-9 may amplify local angiogenesis by cleaving membranebound VEGF. Therefore, VEGF is a candidate to be blocked and controlled and to prevent the activation of the androgen receptor (AR)/phosphatidylinositol 4-phosphate 5-kinase type-1 alpha (PIP5K1α)/AKT/MMP-9/VEGF signaling axis required for cell survival and invasion of metastatic tumors (198). Similarly, the effect of phytochemicals on MMP-2, MMP-9, and their tissue inhibitors (TIMPs) has been tested in breast cancer, with no alterations observed in vitro (199).…”
Section: Therapeutic Perspective Of Mmpsmentioning
confidence: 99%